Two-component polyurethane structural adhesive, preparation method and application thereof

CN122917733APending Publication Date: 2026-10-16WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510436145.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

以动力电池为例,2022年全球动力电池市场量达到104万吨,预计2027年可达到350万吨,而目前动力电池在回收时,普遍采用的除胶方式物理拆除法,即使用机械工具,辅以低温,采用人工拆除的方式,通常需要3周才可完成电池包的完整拆卸,该除胶方法投入较大,且过程繁琐、耗时耗力,难以满足未来大批量回收市场的需求

Benefits of technology

[0057] 1) Wide Substrate Applicability: This invention selects low-polarity polyols, such as polyolefin polyols, dimer polyester polyols, hydroxyl-terminated silicone oils, and hydroxyl acrylates, and combines them with low-polarity aliphatic isocyanate monomers, such as HDI trimers, to reduce the polarity of the polyurethane adhesive and improve its compatibility with low-polarity substrates. This allows for excellent wetting of the surface of low-polarity substrates, and during the compatibility process between the adhesive and the substrate, an interpenetrating network compatibility interface may be formed, thus achieving good adhesion to low-polarity substrates. Furthermore, the urethane groups in the polyurethane adhesive itself can form polar interactions such as hydrogen bonds with high-polarity substrates, thus also exhibiting good adhesion to high-polarity substrates. Therefore, this adhesive has good adhesion to both high and low polarity substrates and is suitable for bonding plastic substrates such as PC/ABS, PC/PET, ASA/PMMA, PP, PC, and PET; metal substrates such as 3003Al and 6061Al; composite materials such as SMC; and glass substrates, demonstrating a wide range of substrate applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005349611970000031
    Figure BDA0005349611970000031
  • Figure BDA0005349611970000032
    Figure BDA0005349611970000032
  • Figure BDA0005349611970000171
    Figure BDA0005349611970000171
Patent Text Reader

Abstract

The application provides a two-component polyurethane structural adhesive as well as a preparation method and application thereof. The polyurethane structural adhesive is composed of component A and component B. The component A comprises the following components: polyester polyol, polyolefin polyol, hydroxyl-terminated silicone oil, chain extender, amino-terminated polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator and thermal expansion microsphere. The component B comprises the following components: polyurethane prepolymer, aliphatic isocyanate monomer, coupling agent, water-removing agent, filler and thixotropic agent. The two-component polyurethane structural adhesive has the advantages of wide substrate applicability, high initial strength and heat-dismounting, and can be applied to the bonding of automobile plastic parts, power batteries and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyurethane adhesive technology, specifically relating to a two-component polyurethane structural adhesive with wide substrate applicability, high initial strength, and heat-disassembly capability, as well as its preparation method and application. Background Technology

[0002] Currently, methods for joining materials are broadly categorized into three types: mechanical joining, welding, and bonding. Among these, bonding offers unparalleled advantages over the other two methods, such as uniform stress distribution, independence from material shape, size, and thickness, resistance to fatigue and alternating loads, good sealing, and the ability to impart special functionalities to materials. Therefore, it has gradually become the most popular joining method in the industrial field. However, due to the wide variety of materials and their significant differences in surface properties, a single adhesive often cannot achieve bonding between different materials. In some cases, no suitable adhesive can be found for certain materials. For some difficult-to-bond materials, such as PET, ABS, and PP, surface treatments like corona discharge and flame welding are necessary before bonding. Improper handling can not only affect the bonding effect but also damage the material's properties. Therefore, obtaining an adhesive with good adhesion to various substrates is a continuous goal pursued by many researchers and is crucial for the effective use of bonding processes.

[0003] Patent CN110699033A describes a polyurethane adhesive for structural bonding between power battery cells or between a cell and a casing. While this adhesive exhibits good adhesion to aluminum and composite materials, its bonding effect on plastic substrates has not been investigated. Patent CN206749482U describes a polyurethane adhesive for bonding automotive plastic tailgates. This adhesive is primarily used for bonding treated PP plastics and does not describe its bonding performance with other plastic or metal substrates.

[0004] Furthermore, in industrial production using adhesive processes, an ideal adhesive needs to possess both a long working period and high initial strength to meet the demands of a fast production cycle requiring sufficient application time and rapid turnover after application. For example, currently, after adhesive application to power battery packs, they typically need to stand for 2 hours to cure and position before being moved to the next process. However, shortening the positioning time to 15 minutes can significantly improve the turnover rate, saving an average of 8-10 million yuan in product costs annually. Similarly, in the bonding of plastic tailgates in automobiles, high-efficiency production lines generally require adhesives to have a working period of more than 3 minutes, and to be able to be handled after holding at 70°C for 3 minutes. However, a long working period and high initial strength are chemically contradictory; this requires the adhesive to have a slow initial reaction rate, followed by a rapid acceleration of the reaction rate after a certain time. Therefore, balancing this contradiction is a major challenge facing the adhesive industry.

[0005] Patent CN111995979B introduces a room temperature fast-curing polyurethane thermally conductive structural adhesive for bonding power battery structures. Although the adhesive can reach a shear strength of 4.5 MPa after 24 hours, it also takes a long time to reach the initial curing strength required for handling, which cannot meet the needs of fast-paced operations.

[0006] Furthermore, with the continuous increase in industrial products, the disposal of end-of-life products has gradually become a social issue. The most important disposal method is recycling, which places new demands on adhesives. Adhesives must maintain good bonding during normal use and, under suitable conditions, quickly detach under appropriate conditions to meet the needs of rapid disassembly of the bonded materials when recycling is required. Taking power batteries as an example, the global power battery market reached 1.04 million tons in 2022 and is projected to reach 3.5 million tons in 2027. Currently, the commonly used method for removing adhesive during power battery recycling is physical disassembly, which involves using mechanical tools, low temperatures, and manual removal. This typically takes three weeks to completely disassemble the battery pack. This method requires significant investment, is cumbersome, time-consuming, and labor-intensive, making it difficult to meet the demands of the future large-scale recycling market.

[0007] Therefore, imparting removability to adhesives is one of the urgent problems to be solved in the adhesive industry today. Summary of the Invention

[0008] In view of the shortcomings of current products, the purpose of this invention is to provide a two-component polyurethane structural adhesive that has the advantages of wide substrate applicability, high initial strength and heat-disassembly capability, and can be used for bonding automotive plastic parts, power batteries and the like.

[0009] Another object of the present invention is to provide a method for preparing such a two-component polyurethane structural adhesive.

[0010] Another object of the present invention is to provide the application of this two-component polyurethane structural adhesive.

[0011] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:

[0012] A two-component polyurethane structural adhesive with wide substrate applicability, high initial strength, and heat-removable design, wherein the two-component polyurethane adhesive is composed of component A and component B;

[0013] The volume ratio of component A to component B is 1:0.9 to 1.1, preferably 1:1;

[0014] Based on the total weight of component A being 100%, component A comprises the following components in weight percentage:

[0015]

[0016] Based on the total weight of component B as 100%, component B comprises the following components in weight percentage:

[0017]

[0018] When using the two-component polyurethane adhesive, components A and B are mixed evenly at a volume ratio of 1:0.9 to 1.1, preferably at a volume ratio of 1:1, and then it is ready for use.

[0019] In some specific embodiments, the polyester polyol in component A is selected from one or more of the following: oxo-based polyester diols (e.g., polyethylene adipate diol), dimer polyester diols (e.g., hexanediol dimer), and polycarbonate diols (e.g., polyhexanediol polycarbonate); dimer polyester diols are preferred. The preferred number-average molecular weight of the polyester polyol is 1000–3000 g / mol.

[0020] In some specific embodiments, the polyolefin polyol in component A is selected from one or more of hydroxyl-terminated polybutadiene, hydroxyl-terminated hydrogenated polybutadiene, hydroxyl-terminated epoxidized polybutadiene, hydroxyl-terminated polybutadiene-acrylonitrile, hydroxyl-terminated styrene-butadiene liquid rubber, hydroxyl-terminated polyisoprene, hydroxyl-terminated hydrogenated polyisoprene, and polystyrene polyol, preferably one or two of hydroxyl-terminated polybutadiene and hydroxyl-terminated hydrogenated polybutadiene; the preferred number average molecular weight of the polyolefin polyol is 2000-3000 g / mol.

[0021] In some specific implementation schemes, the hydroxyl-terminated silicone oil in component A is selected from one or more of hydroxyl-terminated methyl silicone oil, hydroxyl-terminated ethyl silicone oil, hydroxyl-terminated phenyl silicone oil, hydroxyl-terminated methyl phenyl silicone oil, hydroxyl-terminated methyl chlorophenyl silicone oil, hydroxyl-terminated methyl vinyl silicone oil, and bihydroxypropyl silicone oil, preferably hydroxyl-terminated methyl silicone oil; the preferred number average molecular weight of the hydroxyl-terminated silicone oil is 1000-2000 g / mol.

[0022] In some specific embodiments, the chain extender in component A is selected from one or more of ethylene glycol, 1,4-butanediol, diethylene glycol, bisphenol A polyoxyethylene ether, bisphenol A polyoxypropylene ether, 2-ethyl-1,3-hexanediol, trimethylolpropane, glycerol, and triethanolamine, preferably bisphenol A dihydroxypropyl ether.

[0023] In some specific embodiments, the terminal amino polyether in component A is selected from one or more of polypropylene diamine, polypropylene triamine, polyethylene oxide-propylene diamine, polytetrahydrofuran diamine, and polytetramethylene ether di-p-aminobenzoate, preferably polypropylene diamine; the preferred number average molecular weight of the terminal amino polyether is 200-500 g / mol.

[0024] In some specific embodiments, the catalyst in component A is one or more of the following: triethylenediamine, pentamethyldialkyltriamine, N-methylmorpholine, N-methylimidazolium, 1,2-dimethylimidazolium (DMI), DBU, dibutyltin dilaurate, stannous octoate, potassium isooctanoate, and tetrabutyl titanate. Preferably, DMI and DBU are used in combination, with a weight ratio of 1 to 3:1, for example, 2.09 parts: 1 part.

[0025] In some specific implementations, the molecular sieve in component A is one or more of type 3A, 4A, and 5A molecular sieves, preferably 3A molecular sieve;

[0026] In some specific implementation schemes, the fillers in components A and B are one or more of calcium carbonate, calcined kaolin, talc, and aluminum hydroxide, preferably calcium carbonate;

[0027] In some specific implementations, the thixotropic agent in components A and B is one or more of fumed silica, hydrogenated castor oil, polyamide wax, and bentonite, preferably fumed silica;

[0028] In some specific implementations, the thermal initiator in component A is one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutyronitrile cyanoformamide, preferably AIBN;

[0029] In some specific embodiments, the thermally expandable microspheres in component A are thermally expandable microcapsules made by encapsulating a low-boiling-point solvent in a thermoplastic polymer shell, with a maximum foaming temperature of 80-200°C (e.g., 100°C, 110°C, 120°C, 130°C, etc.). The present invention preferably uses thermally expandable microspheres with a maximum foaming temperature of 90-110°C.

[0030] In some specific embodiments, the polyurethane prepolymer in component B is obtained by reacting raw materials including plasticizer, hydroxyl-terminated polybutadiene, hydroxyl acrylate, and isocyanate monomer. Preferably, the weight ratio of plasticizer, hydroxyl-terminated polybutadiene (preferably with a number average molecular weight of 2000-3000 g / mol), hydroxyl acrylate, and isocyanate monomer is 18-21 parts: 46-50 parts: 4-5 parts: 25-30 parts; more preferably, the weight ratio of plasticizer, hydroxyl-terminated polybutadiene, hydroxyl acrylate, and isocyanate monomer is 19 parts: 48 parts: 5 parts: 28 parts.

[0031] The plasticizer is one or more of diisodecyl phthalate (DIDP), diisooctyl phthalate, and diisononyl phthalate, preferably DIDP;

[0032] The hydroxy acrylate is one or more of hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate, and hydroxyethyl acrylate, preferably HEMA;

[0033] The isocyanate monomer is one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), polymethylene polyphenyl isocyanate (PAPI), and carbodiimide-modified MDI. Preferably, carbodiimide-modified MDI and PAPI are used in combination, with a weight ratio of 1 part: 1 part.

[0034] In some specific embodiments, the aliphatic isocyanate monomer in component B is one or more of hexamethylene diisocyanate (HDI), 1,4-cyclohexane diisocyanate, methylcyclohexyl diisocyanate, and HDI trimer, preferably HDI trimer;

[0035] In some specific embodiments, the coupling agent in component B is one or more of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) and γ-isocyanate propyltrimethoxysilane, preferably KH-560;

[0036] In some specific embodiments, the dehydrating agent in component B is one or more of 1,3-oxazolidinyl pentane, p-benzenesulfonyl isocyanate (PTST), and triethyl orthoformate, preferably PTSI.

[0037] In another aspect, the present invention provides a method for preparing the aforementioned two-component polyurethane structural adhesive, including methods for preparing components A and B respectively. In this invention, there are no restrictions on the order of preparation of components A and B; components A and B can be mixed evenly at a volume ratio of 1:0.9 to 1.1 before use.

[0038] In a preferred embodiment, the preparation process of component A is as follows:

[0039] S1: Add polyester polyol, polyolefin polyol and hydroxyl-terminated silicone oil to the reactor, heat up and dehydrate under vacuum.

[0040] S2: Cool down, add chain extender, terminal amino polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator, and thermal expansion microspheres in proportion, control the temperature, and stir under vacuum for a period of time to obtain component A.

[0041] In a preferred embodiment, the preparation process of component B is as follows:

[0042] S1: Add plasticizer, hydroxyl-terminated polybutadiene, and hydroxyl acrylate to the reactor, heat up, and dehydrate under vacuum.

[0043] S2: Add isocyanate monomers and react to prepare polyurethane prepolymer;

[0044] S3: Cool down, add aliphatic isocyanate monomer, coupling agent, dehydrating agent, filler and thixotropic agent in proportion, and stir under vacuum for a period of time to obtain component B.

[0045] In a more preferred embodiment, the method for preparing the two-component polyurethane structural adhesive of the present invention includes the following steps:

[0046] The preparation process of component A is as follows:

[0047] S1: Add polyester polyol, polyolefin polyol and hydroxyl-terminated silicone oil to the reactor, heat to 110-130℃, and dehydrate under vacuum for 1-2 hours;

[0048] S2: Cool down to below 40℃, add chain extender, amino-terminated polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator, and thermal expansion microspheres, and vacuum stir for 1-2 hours to obtain component A. During the stirring process, control the temperature inside the reactor to not exceed 40℃.

[0049] And / or, the preparation process of component B is as follows:

[0050] S1: Add plasticizer, hydroxyl-terminated polybutadiene, and hydroxyl acrylate to the reactor, heat to 110-130℃, and dehydrate under vacuum for 1-2 hours;

[0051] S2: Cool down to below 90℃, add isocyanate monomer, protect with nitrogen, and react at 90-95℃ for 1-2 hours;

[0052] S3: Cool down to below 40℃, add aliphatic isocyanate monomer, coupling agent, dehydrating agent, filler, and thixotropic agent, and stir under vacuum for 1-2 hours to obtain component B.

[0053] Components A and B are packaged separately and mixed at a volume ratio of 1:0.9 to 1.1, preferably 1:1, to obtain a two-component polyurethane structural adhesive.

[0054] In another aspect, the present invention also provides an application of the two-component polyurethane structural adhesive as described above.

[0055] Preferably, the above-mentioned two-component polyurethane structural adhesive is suitable for bonding automotive plastic parts and power batteries.

[0056] Compared with the prior art, the present invention has the following technical effects:

[0057] 1) Wide Substrate Applicability: This invention selects low-polarity polyols, such as polyolefin polyols, dimer polyester polyols, hydroxyl-terminated silicone oils, and hydroxyl acrylates, and combines them with low-polarity aliphatic isocyanate monomers, such as HDI trimers, to reduce the polarity of the polyurethane adhesive and improve its compatibility with low-polarity substrates. This allows for excellent wetting of the surface of low-polarity substrates, and during the compatibility process between the adhesive and the substrate, an interpenetrating network compatibility interface may be formed, thus achieving good adhesion to low-polarity substrates. Furthermore, the urethane groups in the polyurethane adhesive itself can form polar interactions such as hydrogen bonds with high-polarity substrates, thus also exhibiting good adhesion to high-polarity substrates. Therefore, this adhesive has good adhesion to both high and low polarity substrates and is suitable for bonding plastic substrates such as PC / ABS, PC / PET, ASA / PMMA, PP, PC, and PET; metal substrates such as 3003Al and 6061Al; composite materials such as SMC; and glass substrates, demonstrating a wide range of substrate applicability.

[0058] 2) High initial strength: On the one hand, a combined amine (DBU + 1,2-dimethylimidazole) was selected as the preferred catalyst for this system. This catalyst is thermosensitive and exhibits very low catalytic activity for the isocyanate and hydroxyl groups at low temperatures, but its catalytic activity rapidly increases upon heating. On the other hand, a low molecular weight terminal amino polyether was added, which has high reactivity and rapidly forms a large number of urethane hard segments in the initial stage of the reaction, ensuring a rapid increase in the initial strength of the system. In addition, double bonds are introduced into the system by adding hydroxyl acrylate, and a thermal initiator is added. Upon heating, the initiator initiates the opening of the double bonds, resulting in a rapid polymerization reaction. Through the combination of these three aspects, the system exhibits excellent thermosensitivity: after being applied and placed at 70°C for 3 minutes, it reaches a shear strength of 0.6 MPa, thus possessing high initial strength and meeting the needs of fast-paced production.

[0059] 3) Heat-removable: The adhesive is made heat-removable by introducing thermally expanding microspheres into the system. When the cured adhesive is placed at a high temperature, the thermally expanding microspheres in the system expand rapidly, creating more cavities and reducing the bond strength between the adhesive and the substrate. Therefore, when disassembly is required, it can be quickly completed by brief heating without affecting the substrate. Experimental results show that after being placed at 100℃ for 10 minutes, the peel strength can be reduced to 0.9 N / mm.

[0060] It should be noted that the above-mentioned technical effects of the present invention are all due to the combined effect and mutual cooperation of the components in the two-component polyurethane structural adhesive. Detailed Implementation

[0061] To enable those skilled in the art to better understand the present invention, the present invention will be described in detail below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0062] The raw materials are sourced as follows:

[0063] Polyester polyol: molecular weight 2000 g / mol, hydroxyl value 55 mg KOH / g, Shanghai Jingri New Material Technology Co., Ltd.: DA-21;

[0064] Polyolefin polyol: molecular weight 2800 g / mol, hydroxyl value 47.69 mg KOH / g, Cray Valley: Poly bd R-45HTLO, hydroxyl-terminated polybutadiene;

[0065] Hydroxyl-terminated silicone oil: molecular weight 1000g / mol, hydroxyl value 148.53mgKOH / g, Anhui Aiyota Silicone Oil Co., Ltd.: IOTA2030, double-terminated hydroxypropyl silicone oil;

[0066] Chain extender: molecular weight 390g / mol, hydroxyl value 280mgKOH / g, Hubei Guangao Biotechnology Co., Ltd.: DIO330, bisphenol A polyoxypropylene ether;

[0067] Amino-terminated polyether: molecular weight 230 g / mol, hydroxyl value 487.8 KOH / g, Wanhua Chemical Group Co., Ltd. 8100;

[0068] Catalyst: DMI: Toyocat DM70 (Tosoh Corporation, Japan); DBU: Polycat DBU (Air Products); DMI and DBU are used at a mass ratio of 2:1.

[0069] Molecular sieve: Arkema: SA1720;

[0070] Filler: Omyacard 520 (Omya Calcium Industry Co., Ltd.);

[0071] Thixotropic agent: Degussa: AEROSIL R202;

[0072] Thermal initiator: Jinan Century Tongda Chemical Co., Ltd.: V-60;

[0073] Thermally expandable microspheres: Polychem: 120DU15;

[0074] Plasticizer: ExxonMobil: Jayflex TM DIDP;

[0075] Hydroxyacrylates: Jiangsu Pules Biotechnology Co., Ltd.: Hydroxyethyl methacrylate;

[0076] Isocyanate monomer: Carbodiimide modified MDI: Wanhua Chemical Group Co., Ltd. CDMDI-100E; PAPI: Wanhua Chemical Group Co., Ltd. PM-200. Use both at a 1:1 weight ratio.

[0077] Aliphatic isocyanate monomers: Wanhua Chemical Group Co., Ltd. HT-100;

[0078] Coupling agent: Momentive Pharmaceuticals, USA: Silquest A-187;

[0079] Dehydrating agent: Hangzhou Yilian Chemical Co., Ltd.: p-Benzylsulfonyl isocyanate;

[0080] Unless otherwise specified, all other raw materials are from commercially available products.

[0081] Example 1

[0082] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 26.12 parts, polyolefin polyol: 20.90 parts, hydroxyl-terminated silicone oil: 5.22 parts, chain extender: 2.61 parts, amino-terminated polyether: 2.61 parts, catalyst: 2.05 parts, molecular sieve: 4.70 parts, filler: 23.51 parts, thixotropic agent: 0.52 parts, thermal initiator: 1.31 parts, and thermally expandable microspheres: 10.45 parts;

[0083] In this embodiment, component B comprises the following components in parts by weight: polyurethane prepolymer: 51.67 parts, aliphatic isocyanate monomer: 5.19 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 40.54 parts, thixotropic agent: 0.49 parts;

[0084] The polyurethane prepolymer is obtained by reacting 19 parts of plasticizer, 48 parts of hydroxyl-terminated polybutadiene, 5 parts of hydroxyl acrylate, and 28 parts of isocyanate monomer.

[0085] In this embodiment, component A is prepared in the following manner:

[0086] Polyester polyol, polyolefin polyol, and hydroxyl-terminated silicone oil were added to the reactor. The temperature was raised to 120°C, and after vacuum dehydration for 2 hours, the temperature was lowered to 30°C. Chain extender, amino-terminated polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator, and thermally expanding microspheres were added. The reactor was stirred under vacuum, and the temperature inside the reactor was controlled not to exceed 40°C during the stirring process. After stirring for 1.5 hours, component A was discharged.

[0087] In this embodiment, component B is prepared in the following manner:

[0088] Plasticizer, hydroxyl-terminated polybutadiene, and hydroxyl acrylate were added to the reactor. The temperature was raised to 120°C, and after vacuum dehydration for 2 hours, the temperature was lowered to 80°C. Isocyanate monomers were added, and under nitrogen protection, the temperature was controlled at 95°C for 2 hours. Then, the temperature was lowered to 30°C, and aliphatic isocyanate monomers, coupling agents, dehydrating agents, fillers, and thixotropic agents were added. After vacuum stirring for 1 hour, component B was discharged.

[0089] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0090] Example 2

[0091] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 30.37 parts, polyolefin polyol: 24.30 parts, hydroxyl-terminated silicone oil: 6.07 parts, chain extender: 3.04 parts, amino-terminated polyether: 3.04 parts, catalyst: 2.39 parts, molecular sieve: 5.47 parts, filler: 16.86 parts, thixotropic agent: 0.61 parts, thermal initiator: 1.52 parts, and thermally expandable microspheres: 6.34 parts;

[0092] In this embodiment, component B comprises the following components in parts by weight: polyurethane prepolymer: 40.37 parts, aliphatic isocyanate monomer: 8.44 parts, coupling agent: 1.62 parts, dehydrating agent: 0.35 parts, filler: 48.76 parts, thixotropic agent: 0.46 parts;

[0093] The composition of the polyurethane prepolymer in this embodiment is the same as that in Example 1.

[0094] In this embodiment, the preparation methods of components A and B are the same as in Example 1.

[0095] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0096] Example 3

[0097] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 23.75 parts, polyolefin polyol: 19.00 parts, hydroxyl-terminated silicone oil: 4.75 parts, chain extender: 2.37 parts, amino-terminated polyether: 2.37 parts, catalyst: 1.87 parts, molecular sieve: 4.27 parts, filler: 30.46 parts, thixotropic agent: 0.47 parts, thermal initiator: 1.19 parts, and thermally expandable microspheres: 9.50 parts;

[0098] In this embodiment, component B comprises the following components in parts by weight: polyurethane prepolymer: 58.61 parts, aliphatic isocyanate monomer: 3.96 parts, coupling agent: 1.64 parts, dehydrating agent: 0.35 parts, filler: 34.97 parts, thixotropic agent: 0.47 parts;

[0099] The composition of the polyurethane prepolymer in this embodiment is the same as that in Example 1.

[0100] In this embodiment, the preparation methods of components A and B are the same as in Example 1.

[0101] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0102] Example 4

[0103] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 13.00 parts, polyolefin polyol: 32.00 parts, hydroxyl-terminated silicone oil: 7.22 parts, chain extender: 2.61 parts, amino-terminated polyether: 2.61 parts, catalyst: 2.05 parts, molecular sieve: 4.70 parts, filler: 23.51 parts, thixotropic agent: 0.52 parts, thermal initiator: 1.31 parts, and thermally expandable microspheres: 10.45 parts;

[0104] In this embodiment, component B comprises the following components in parts by weight: polyurethane prepolymer: 51.67 parts, aliphatic isocyanate monomer: 5.19 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 40.54 parts, thixotropic agent: 0.49 parts;

[0105] The composition of the polyurethane prepolymer in this embodiment is the same as that in Example 1.

[0106] In this embodiment, the preparation methods of components A and B are the same as in Example 1.

[0107] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0108] Example 5

[0109] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 35.36 parts, polyolefin polyol: 13.14 parts, hydroxyl-terminated silicone oil: 3.24 parts, chain extender: 2.64 parts, amino-terminated polyether: 2.64 parts, catalyst: 2.07 parts, molecular sieve: 4.75 parts, filler: 23.75 parts, thixotropic agent: 0.53 parts, thermal initiator: 1.32 parts, and thermally expandable microspheres: 10.56 parts;

[0110] The composition and preparation method of component B in this embodiment are the same as in Example 1.

[0111] In this embodiment, the preparation method of component A is the same as that in Example 1.

[0112] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0113] Example 6

[0114] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 26.26 parts, polyolefin polyol: 21.01 parts, hydroxyl-terminated silicone oil: 5.25 parts, chain extender: 3.92 parts, amino-terminated polyether: 1.31 parts, catalyst: 2.06 parts, molecular sieve: 4.73 parts, filler: 23.63 parts, thixotropic agent: 0.53 parts, thermal initiator: 0.80 parts, and thermally expandable microspheres: 10.50 parts;

[0115] The composition and preparation method of component B in this embodiment are the same as in Example 1.

[0116] In this embodiment, the preparation method of component A is the same as that in Example 1.

[0117] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0118] Example 7

[0119] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 26.21 parts, polyolefin polyol: 20.97 parts, hydroxyl-terminated silicone oil: 5.24 parts, chain extender: 1.20 parts, amino-terminated polyether: 3.31 parts, catalyst: 2.06 parts, molecular sieve: 4.72 parts, filler: 23.59 parts, thixotropic agent: 0.52 parts, thermal initiator: 1.71 parts, and thermally expandable microspheres: 10.48 parts;

[0120] The composition and preparation method of component B in this embodiment are the same as in Example 1.

[0121] In this embodiment, the preparation method of component A is the same as that in Example 1.

[0122] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0123] Example 8

[0124] In this embodiment, component A comprises the following components in parts by weight: polyester polyol: 26.12 parts, polyolefin polyol: 20.90 parts, hydroxyl-terminated silicone oil: 5.22 parts, chain extender: 2.61 parts, amino-terminated polyether: 2.61 parts, catalyst: 2.05 parts, molecular sieve: 4.70 parts, filler: 18.51 parts, thixotropic agent: 0.52 parts, thermal initiator: 1.31 parts, and thermally expandable microspheres: 15.45 parts;

[0125] The composition and preparation method of component B in this embodiment are the same as in Example 1.

[0126] In this embodiment, the preparation method of component A is the same as that in Example 1.

[0127] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0128] Comparative Example 1

[0129] This comparative example uses conventional polyester polyol castor oil as the white component in the adhesive system.

[0130] In this comparative example, component A contains the following components in parts by weight: castor oil: 63.72 parts, chain extender: 6.37 parts, catalyst: 2.50 parts, molecular sieve: 5.74 parts, filler: 21.03 parts, thixotropic agent: 0.64 parts;

[0131] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 50.18 parts, coupling agent: 1.66 parts, dehydrating agent: 0.36 parts, filler: 47.34 parts, thixotropic agent: 0.47 parts;

[0132] The polyurethane prepolymer was obtained by reacting 37.73 parts of castor oil and 62.26 parts of isocyanate monomer: castor oil was added to the reactor, the temperature was raised to 120°C, and after vacuum dehydration for 2 hours, the temperature was lowered to 80°C, the isocyanate monomer was added, and under nitrogen protection, the temperature was controlled at 95°C for 2 hours to obtain the polyurethane prepolymer.

[0133] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0134] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0135] Comparative Example 2

[0136] This comparative example uses polyolefin polyols as the white component in the adhesive system.

[0137] In this comparative example, component A contains the following components in parts by weight: polyolefin polyol: 61.76 parts, chain extender: 6.18 parts, catalyst: 2.43 parts, molecular sieve: 5.56 parts, filler: 23.47 parts, thixotropic agent: 0.62 parts;

[0138] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 47.86 parts, coupling agent: 1.66 parts, dehydrating agent: 0.35 parts, filler: 49.66 parts, thixotropic agent: 0.47 parts;

[0139] The polyurethane prepolymer was obtained by reacting 19.27 parts of plasticizer, 54.35 parts of polyolefin polyol, and 26.38 parts of isocyanate monomer.

[0140] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0141] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0142] Comparative Example 3

[0143] This comparative example adds polyester polyol as the white component in the adhesive system to the basis of comparative example 2.

[0144] In this comparative example, component A contains the following components in parts by weight: 29.95 parts polyester polyol, 29.95 parts polyolefin polyol, 5.99 parts chain extender, 2.35 parts catalyst, 5.39 parts molecular sieve, 25.76 parts filler, and 0.60 parts thixotropic agent;

[0145] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 49.94 parts, coupling agent: 1.71 parts, dehydrating agent: 0.37 parts, filler: 47.50 parts, thixotropic agent: 0.45 parts;

[0146] The polyurethane prepolymer was obtained by reacting 19.02 parts of plasticizer, 53.66 parts of polyolefin polyol, and 27.32 parts of isocyanate monomer.

[0147] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0148] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0149] Comparative Example 4

[0150] This comparative example adds an aliphatic isocyanate monomer as a black component to the comparative example 3.

[0151] In this comparative example, component A contains the following components in parts by weight: 29.08 parts polyester polyol, 29.08 parts polyolefin polyol, 5.82 parts chain extender, 2.28 parts catalyst, 5.23 parts molecular sieve, 27.92 parts filler, and 0.58 parts thixotropic agent;

[0152] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 47.07 parts, aliphatic isocyanate monomer: 4.14 parts, coupling agent: 1.71 parts, dehydrating agent: 0.37 parts, filler: 46.29 parts, thixotropic agent: 0.49 parts;

[0153] The polyurethane prepolymer is obtained by reacting 20.21 parts of plasticizer, 56.99 parts of polyolefin polyol, and 22.80 parts of isocyanate monomer.

[0154] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0155] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0156] Comparative Example 5

[0157] This comparative example adds hydroxyl acrylate to the prepolymerization reaction component of the polyurethane prepolymer, based on Comparative Example 4.

[0158] In this comparative example, component A contains the following components in parts by weight: 27.26 parts polyester polyol, 27.26 parts polyolefin polyol, 5.45 parts chain extender, 2.14 parts catalyst, 4.91 parts molecular sieve, 32.44 parts filler, and 0.55 parts thixotropic agent;

[0159] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 49.20 parts, aliphatic isocyanate monomer: 4.94 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 43.26 parts, thixotropic agent: 0.49 parts;

[0160] The polyurethane prepolymer is obtained by reacting 19.60 parts of plasticizer, 50.25 parts of polyolefin polyol, 5.02 parts of hydroxyl acrylate, and 25.12 parts of isocyanate monomer.

[0161] The preparation method of the polyurethane prepolymer in this comparative example is the same as that in Example 1.

[0162] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0163] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0164] Comparative Example 6

[0165] This comparative example adds hydroxyl-terminated silicone oil as a white component to the basic comparative example 5.

[0166] In this comparative example, component A contains the following components in parts by weight: 26.54 parts polyester polyol, 21.23 parts polyolefin polyol, 5.31 parts hydroxyl-terminated silicone oil, 5.31 parts chain extender, 2.08 parts catalyst, 4.78 parts molecular sieve, 34.23 parts filler, and 0.53 parts thixotropic agent;

[0167] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 50.55 parts, aliphatic isocyanate monomer: 4.93 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 41.92 parts, thixotropic agent: 0.49 parts;

[0168] The polyurethane prepolymer was obtained by reacting 19.03 parts of plasticizer, 48.79 parts of polyolefin polyol, 4.88 parts of hydroxyl acrylate, and 27.32 parts of isocyanate monomer.

[0169] The preparation method of the polyurethane prepolymer in this comparative example is the same as that in Example 1.

[0170] In this comparative example, the preparation methods of components A and B are the same as in Example 1.

[0171] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0172] Comparative Example 7

[0173] This comparative example uses a conventional catalyst (dibutyltin dilaurate) instead of the thermosensitive catalyst in comparative example 6.

[0174] In this comparative example, component A contains the following components in parts by weight: 27.06 parts polyester polyol, 21.65 parts polyolefin polyol, 5.41 parts hydroxyl-terminated silicone oil, 5.41 parts chain extender, 0.14 parts dibutyltin dilaurate, 4.87 parts molecular sieve, 34.91 parts filler, and 0.54 parts thixotropic agent;

[0175] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 50.55 parts, aliphatic isocyanate monomer: 4.93 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 41.92 parts, thixotropic agent: 0.49 parts;

[0176] The polyurethane prepolymer was obtained by reacting 19.03 parts of plasticizer, 48.79 parts of polyolefin polyol, 4.88 parts of hydroxyl acrylate, and 27.32 parts of isocyanate monomer.

[0177] The composition and preparation method of component B in this comparative example are the same as those in comparative example 6.

[0178] The composition of the polyurethane prepolymer in this comparative example is the same as that in Comparative Example 6.

[0179] In this comparative example, component A was prepared in the same manner as in Example 1.

[0180] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0181] Comparative Example 8

[0182] This comparative example adds terminal amino polyether as a white component to the basic comparative example 7.

[0183] In this comparative example, component A contains the following components in parts by weight: polyester polyol 26.12 parts, polyolefin polyol 20.90 parts, hydroxyl-terminated silicone oil 5.22 parts, chain extender 2.61 parts, amino-terminated polyether 2.61 parts, catalyst 2.05 parts, molecular sieve 4.70 parts, filler 35.26 parts, and thixotropic agent 0.52 parts;

[0184] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 51.67 parts, aliphatic isocyanate monomer: 5.19 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 40.54 parts, thixotropic agent: 0.49 parts;

[0185] The polyurethane prepolymer is obtained by reacting 18.66 parts of plasticizer, 47.85 parts of polyolefin polyol, 4.78 parts of hydroxyl acrylate, and 28.71 parts of isocyanate monomer.

[0186] The preparation method of the polyurethane prepolymer in this comparative example is the same as that in Example 1.

[0187] In this comparative example, components A and B are prepared in the same manner as in Example 1.

[0188] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0189] Comparative Example 9

[0190] This comparative example is based on Comparative Example 8 with the addition of a thermal initiator.

[0191] In this comparative example, component A contains the following components in parts by weight: 26.12 parts polyester polyol, 20.90 parts polyolefin polyol, 5.22 parts hydroxyl-terminated silicone oil, 2.61 parts chain extender, 2.61 parts amino-terminated polyether, 2.05 parts catalyst, 4.70 parts molecular sieve, 33.96 parts filler, 0.52 parts thixotropic agent, and 1.31 parts thermal initiator;

[0192] In this comparative example, component B contains the following components in parts by weight: polyurethane prepolymer: 51.67 parts, aliphatic isocyanate monomer: 5.19 parts, coupling agent: 1.73 parts, dehydrating agent: 0.37 parts, filler: 40.54 parts, thixotropic agent: 0.49 parts;

[0193] The polyurethane prepolymer is obtained by reacting 18.66 parts of plasticizer, 47.85 parts of polyolefin polyol, 4.78 parts of hydroxyl acrylate, and 28.71 parts of isocyanate monomer.

[0194] The composition and preparation method of component B in this comparative example are the same as those in comparative example 8.

[0195] The composition of the polyurethane prepolymer in this comparative example is the same as that in Comparative Example 8.

[0196] In this comparative example, component A was prepared in the same manner as in Example 1.

[0197] When using, components A and B should be mixed evenly at a volume ratio of 1:1.

[0198] Test method:

[0199] In this scheme, the tensile strength, elongation at break, final shear strength, operating period, initial shear strength, and peel strength after high temperature of the samples were tested respectively.

[0200] Tensile strength and elongation at break: Refer to GB / T 528-2009.

[0201] Shear strength: Tensile shear strength was tested according to GB / T 7124-2008. PC / ABS, PC / PET, ASA / PMMA, PP (flame treated), PC, PET, 3003Al, 6061Al, Glass, and SMC were selected as adhesive substrates for the experiment. After the test, the failure state of the adhesive layer was observed and recorded: interfacial failure (AF) or cohesive failure (CF).

[0202] Operating period: GB / T 7123.1-2016.

[0203] Initial shear strength: Tensile shear strength was tested according to GB / T 7124-2008. PC was used as the bonding substrate in the experiment. After the shear sample was prepared, it was immediately placed in a 70℃ oven and kept at that temperature for 3 minutes. After that, it was taken out and placed at room temperature for 3 minutes before the shear strength was tested.

[0204] Peel strength after high temperature: Peel strength was tested according to GB / T 2791-1995. 6061Al was used as the bonding substrate. After the T-shaped peel sample was prepared, it was cured at room temperature for 7 days, then placed in a 100℃ oven for 10 minutes and removed. After being placed at room temperature for 1 hour, the peel strength was tested.

[0205] Table 1. Test results of the two-component polyurethane structural adhesive in the examples.

[0206]

[0207]

[0208] Table 2. Test results of comparative example two-component polyurethane structural adhesives

[0209]

[0210]

[0211] As can be seen from the experimental data in Tables 1 and 2, compared with Comparative Examples 1-4, the Example, through the screening of black and white materials, selected polyester polyol + polyolefin polyol + hydroxyl-terminated silicone oil + hydroxyl acrylate as the white material combination, and added aliphatic isocyanate monomers to the black material, achieving effective bonding to various plastic substrates, metal substrates, glass substrates, and composite materials. Upon failure, CF destruction was achieved, indicating that the adhesive has broad substrate applicability. Compared with Comparative Examples 5-8, the Example, by selecting a temperature-sensitive catalyst, adding low molecular weight terminal amino polyether, and introducing double bonds, achieved excellent temperature sensitivity. After 70℃ treatment for 3 minutes after application, the shear strength reached 0.6 MPa, indicating that the adhesive has high initial strength and can meet the needs of fast-paced production. Compared with Comparative Example 9, the Example, by adding thermally expanding microspheres, showed that the peel strength of the bonding system decreased to below 0.9 N / mm after a short high-temperature treatment, indicating that the adhesive has heat-removable properties and meets the needs of substrate recycling.

[0212] In summary, by selecting appropriate black and white materials, using suitable temperature-sensitive systems, adding thermally expanding microspheres, and rationally combining the components, the two-component polyurethane structural adhesive of this invention has achieved the advantages of wide substrate applicability, high initial strength, and heat-disassembly capability, making it suitable for bonding automotive plastic parts, power batteries, and the like.

[0213] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A two-component polyurethane structural adhesive, wherein the two-component polyurethane adhesive is composed of component A and component B; The volume ratio of component A to component B is 1:0.9 to 1.1, preferably 1:1; Based on the total weight of component A being 100%, component A comprises the following components in weight percentage: Based on the total weight of component B as 100%, component B comprises the following components in weight percentage:

2. The two-component polyurethane adhesive according to claim 1, characterized in that, The polyester polyol in component A is selected from one or more of the following: oxo-based polyester diols (e.g., polyethylene adipate diol), dimer polyester diols (e.g., hexanediol dimer), and polycarbonate diols (e.g., polyhexanediol polycarbonate diol). The preferred number-average molecular weight of polyester polyols is 1000–3000 g / mol; and / or The polyolefin polyol in component A is selected from one or more of the following: hydroxyl-terminated polybutadiene, hydroxyl-terminated hydrogenated polybutadiene, hydroxyl-terminated epoxidized polybutadiene, hydroxyl-terminated polybutadiene-acrylonitrile, hydroxyl-terminated styrene-butadiene liquid rubber, hydroxyl-terminated polyisoprene, hydroxyl-terminated hydrogenated polyisoprene, and polystyrene polyol; the preferred number average molecular weight of the polyolefin polyol is 2000-3000 g / mol.

3. The two-component polyurethane adhesive according to claim 1, characterized in that, The hydroxyl-terminated silicone oil in component A is selected from one or more of the following: hydroxyl-terminated methyl silicone oil, hydroxyl-terminated ethyl silicone oil, hydroxyl-terminated phenyl silicone oil, hydroxyl-terminated methylphenyl silicone oil, hydroxyl-terminated methylchlorophenyl silicone oil, hydroxyl-terminated methyl vinyl silicone oil, and double-terminated hydroxypropyl silicone oil; the preferred number-average molecular weight of the hydroxyl-terminated silicone oil is 1000-2000 g / mol. And / or: The chain extender in component A is selected from one or more of ethylene glycol, 1,4-butanediol, diethylene glycol, bisphenol A polyoxyethylene ether, bisphenol A polyoxypropylene ether, 2-ethyl-1,3-hexanediol, trimethylolpropane, glycerol, and triethanolamine; and / or The amino-terminated polyether in component A is selected from one or more of polypropylene diamine, polypropylene triamine, ethylene oxide-propylene diamine, polytetrahydrofuran diamine, and polytetramethylene ether di-p-aminobenzoate; the preferred number-average molecular weight of the amino-terminated polyether is 200-500 g / mol. and / or The catalyst in component A is one or more of the following: triethylenediamine, pentamethyldialkyltriamine, N-methylmorpholine, N-methylimidazolium, 1,2-dimethylimidazolium (DMI), DBU, dibutyltin dilaurate, stannous octoate, potassium isooctanoate, and tetrabutyl titanate. Preferably, DMI and DBU are used in combination, with a weight ratio of 1 to 3:

1. and / or The molecular sieve in component A is one or more of the following types: 3A, 4A, and 5A.

4. The two-component polyurethane adhesive according to claim 1, characterized in that, The fillers in components A and B are one or more of calcium carbonate, calcined kaolin, talc, and aluminum hydroxide; and / or The thixotropic agents in components A and B are one or more of fumed silica, hydrogenated castor oil, polyamide wax, and bentonite.

5. The two-component polyurethane adhesive according to claim 1, characterized in that, The thermally expandable microspheres in component A are thermally expandable microcapsules made by encapsulating a low-boiling-point solvent in a thermoplastic polymer shell, with a maximum foaming temperature of 80–200°C, preferably 90–110°C; and / or The thermal initiator in component A is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azoisobutyronitrile cyanoformamide.

6. The two-component polyurethane adhesive according to claim 1, characterized in that, The polyurethane prepolymer in component B is obtained by reacting raw materials including plasticizer, hydroxyl-terminated polybutadiene, hydroxyl acrylate, and isocyanate monomer I. Preferably, the weight ratio of plasticizer, hydroxyl-terminated polybutadiene (preferably with a number average molecular weight of 2000-3000 g / mol), hydroxy acrylate, and isocyanate monomer I is 18-21:46-50:4-5:25-30; Preferably, the plasticizer is one or more of diisodecyl phthalate, diisooctyl phthalate, and diisononyl phthalate; Preferably, the hydroxy acrylate is one or more of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxyethyl acrylate; Preferably, the isocyanate monomer I is one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, polymethylene polyphenyl isocyanate, and carbodiimide-modified MDI.

7. The two-component polyurethane adhesive according to claim 1, characterized in that, The aliphatic isocyanate monomer in component B is one or more of hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexyl diisocyanate, and HDI trimer.

8. The two-component polyurethane adhesive according to claim 1, characterized in that, The coupling agent in component B is one or more of γ-glycidoxypropyltrimethoxysilane and γ-isocyanate propyltrimethoxysilane.

9. The two-component polyurethane adhesive according to claim 1, characterized in that, The dehydrating agent in component B is one or more of 1,3-oxazolidinyl pentane, p-benzenesulfonyl isocyanate, and triethyl orthoformate.

10. A method for preparing a two-component polyurethane structural adhesive according to any one of claims 1-9, comprising: The preparation process of component A includes: S1: Add polyester polyol, polyolefin polyol and hydroxyl-terminated silicone oil to the reactor, heat up and dehydrate under vacuum. S2: Cool down, add chain extender, terminal amino polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator, and thermal expansion microspheres in proportion, control the temperature, and stir under vacuum for a period of time to obtain component A; The preparation process of component B includes: S1: Add plasticizer, hydroxyl-terminated polybutadiene, and hydroxyl acrylate to the reactor, heat up, and dehydrate under vacuum. S2: Add isocyanate monomer I and react to prepare polyurethane prepolymer; S3: Cool down, add aliphatic isocyanate monomer, coupling agent, dehydrating agent, filler and thixotropic agent in proportion, and stir under vacuum for a period of time to obtain component B; Preferably, the preparation method of the two-component polyurethane structural adhesive includes the following steps: The preparation process of component A includes: S1: Add polyester polyol, polyolefin polyol and hydroxyl-terminated silicone oil to the reactor, heat to 110-130℃, and dehydrate under vacuum for 1-2 hours; S2: Cool down to below 40℃, add chain extender, amino-terminated polyether, catalyst, molecular sieve, filler, thixotropic agent, thermal initiator, and thermal expansion microspheres, and vacuum stir for 1-2 hours to obtain component A. During the stirring process, control the temperature inside the reactor to not exceed 40℃. The preparation process of component B includes: S1: Add plasticizer, hydroxyl-terminated polybutadiene, and hydroxyl acrylate to the reactor, heat to 110-130℃, and dehydrate under vacuum for 1-2 hours; S2: Cool down to below 90℃, add isocyanate monomer I, under nitrogen protection, and control the temperature at 90-95℃ for 1-2 hours; S3: Cool down to below 40℃, add aliphatic isocyanate monomer, coupling agent, dehydrating agent, filler, and thixotropic agent, and stir under vacuum for 1-2 hours to obtain component B.

Citation Information

Patent Citations

  • Two-component polyurethane adhesive, preparation method and applications thereof

    CN110699033A

  • Auto plastic tail -gate connecting device

    CN206749482U